PEMBENTUKAN KARAKTER ISLAMI DALAM KEGIATAN PEMBELAJARAN DI TK IT BINA 45 PONTIANAK - Jakiah, Daeng; Halida, Halida; Lumanulhakim, Lumanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this study is to know: 1) Learning planning with cutting and sticking activities to improve fine motor skills 2) Implementation of learning through cutting and sticking activities to improve fine motor skills 3) Improvement of fine motor skills of children after following cutting and sticking activities. The form of this research is classroom action research with descriptive method. The steps used in this study are as follows: 1). Planning, 2). Implementation, 3). Observation 4). Reflection. The results showed that 1) Learning planning using cutting and sticking techniques to improve fine motor in accordance with the steps that have been determined in improving the fine motor in the cycle 1 and cycle II. with well-crafted categories. 2) Implementation of learning using cutting and sticking techniques to improve fine motor has been implemented by teachers well in accordance with the prepared planning, both in cycle I and cycle II and 3) Improvement of fine motor development of children after following learning by cutting and sticking techniques, developing very good in the first cycle of 59.29 and increase cycle II to 89.41. This means the fine motor of the child has improved very wellÂ Keywords: Smooth Motorcycle, Cutting, Sticking.